Analisis Kualitas Laporan Keuangan pada Bank Perkreditan Rakyat di Kecamatan Sukawati - Ida Ayu Nyoman Yuliastuti; Ni Wayan Anggi Eswarani; Luh Komang Merawati (Forum Kerjasama Pendidikan Tinggi, 2022)
The research objective was to test and obtain empirical evidence whether information systems, human resource quality, internal control systems, good corporate governance, and risk management affect the quality of financial reports at BPRs in Sukawati District. The population in this study were all employees working in 15 BPR units in Sukawati District, totaling 538 people. Samples were taken using a purposive sampling method so as to get 62 people as a sample, multiple linear regression analysis was used to analyze the data. Based on the results of the analysis, it shows that information systems, human resource quality, and risk management have a positive effect on the quality of financial reports at BPRs in the Sukawati District, while the internal control system and good corporate governance have no effect on the quality of financial reports at BPRs in the Sukawati District.